Longitudinal Associations of Perceived Social Inequality and Subjective Socioeconomic Status with Anxiety and Depression in University Students - Noh, Hae-lim; Shim, Eun-Jung (Seuteureseu yeon-gu (Online), 2021)
Background: This study examined the longitudinal associations of perceived social inequality (PSI) and subjective socioeconomic status (SSS) with anxiety and depression. Methods: Data were collected across three time-points over a full semester in 2016 in South Korea. Participants completed an online self-report survey, and data from 247 participants were analyzed. Results: Older age was associated with lower PSI in treatment of women, and higher SSS was associated with lower overall PSI, particularly regarding the opportunity for advancement and law enforcement. Generalized estimating equation (GEE) analyses indicated that higher PSI was associated with clinical depression (OR=1.56) and lower SSS with clinical anxiety (OR=1.39) and depression (OR=1.38). Female students were also associated with clinical anxiety (OR=5.89) and depression at a marginally significant level (OR=1.93). Higher odds of anxiety were observed in students whose mothers have a high-school education as compared to those whose mothers have a university education or above (OR=2.29). Conclusions: Current results suggest the need to address the perceived social inequality and subjective socioeconomic status in the management of anxiety and depression in university students KCI Citation Count: 1